Modelling and regulation of two mechanical systems. Issue 5 (1st August 2018) - Rubio, José de Jesús; Pieper, Jeff; Meda‐Campaña, Jesús A.; Aguilar, Arturo; Rangel, Vanya I.; Gutierrez, Guadalupe Juliana
Abstract : In this work, the modelling and regulation of two mechanical systems are studied. The model is employed to describe the system dynamic behaviour. The regulator is employed to force the system states to track constantly wanted signals. The stability of the advised regulator is analysed via the Lyapunov technique. The recommended strategy is applied to a magnetic generator and in a hexarotor.